Process of translation and cross-cultural adaptation of two Australian instruments to evaluate the physician-pharmacist collaboration in Germany - Weißenborn, Marina; Krass, Ines; Van, Connie; Dähne, Anna; Ritter, Christoph; Haefeli, Walter E.; Seidling, Hanna (Research in social and administrative pharmacy, 2020)
Background - Building interprofessional working relationships between physicians and pharmacists is essential to ensure high-quality patient care. To assess which factors influence the performance and success of their collaboration, validated instruments should be used, such as the Australian “Attitudes Toward Collaboration Instrument (ATCI)” and the “Frequency of Interprofessional Collaboration Instrument (FICI)”. Both instruments were already translated in a previous German study, but not pretested for comprehensibility or cultural appropriateness to ensure that the target group is able to adequately answer the translated items. - Objectives - To translate and particularly cross-culturally adapt two Australian instruments measuring physicians' and pharmacists’ attitudes towards interprofessional collaboration and the frequency of their interactions for use in Germany. - Methods - The ATCI and FICI were translated following internationally recognised guidelines. Two-step cognitive interviewing was performed with physicians and pharmacists working in ambulatory care in Germany. The “Standards for Reporting Qualitative Research” were used to report this study. - Results - Overall, 2 forward and 2 back translations, and 38 cognitive interviews, i.e. cognitive probing (N=10) and behaviour observation (N=28), with 18 physicians and 20 pharmacists were performed. Experts discussed all potential changes. The ATCI and FICI were translated introducing 15 minor (e.g. paraphrasing, item order) and 6 major (e.g. 2 more items in FICI, additional response options) adaptations. The ATCI-P/GP-German and FICI-P/GP-German were found to be easy to answer and clearly-phrased. - Conclusion - This study shows the importance of using recognised methods to translate and adapt questionnaires, consisting of at least four steps: forward translation, back translation, cognitive interviewing and finalisation (each reviewed by an expert panel making their decisions by consensus). A profoundly pretested German-speaking instrument is now available to evaluate and describe interprofessional collaboration between physicians and pharmacists. However, collecting further sociodemographic and contextual information seems necessary for enhanced interpretation of future results.
Available online 23 March 2019
Gesehen am 14.01.2020